Early life history of fishes and zooplankton availability in a Neotropical floodplain: predator–prey functional relationships. (21st November 2018) - da Silva, Jislaine Cristina; Bialetzki, Andréa
Abstract: The variations in the abundance of fish larvae can be dependent on the availability and population dynamics of their prey. Thus, our goal was to investigate the predator–prey relationship by analyzing the occurrence and diets of Hypophthalmus oremaculatus and Plagioscion squamosissimus larvae (zooplanktivorous predators) as well as the availability of their prey (zooplankton). We carried out monthly samplings of larvae and zooplankton. The predator–prey concentrations significantly temporally varied among months, and abundance peaks only synchronized between P. squamosissimus and the potential Cladocera and Copepoda prey. Hypophthalmus oremaculatus consumed and strongly selected Cladocera and Rotifera, while P. squamosissimus selectively based its diet on Cladocera and Copepoda. Functional relationships were found for P. squamosissimus and the consumed Cladocera and Copepoda prey. Our initial hypothesis of a predator–prey functional relationship was confirmed for P. squamosissimus, and this synchronism indicates high reproductive and feeding flexibility in this species. Hypophthalmus oremaculatus did not show a relationship with the concentrations of any of its prey, which may be associated with morphological and environmental constraints.